Transitioning MSMEs to the Normal Tax System - Susilawati, Neni; Herdona, Syadesa Anida; Lim, Vallencia; Nadilla, Choirunnisa (Journal of Economics and Behavioral Studies, 2022)
It is not straightforward to urge and prepare MSMEs to participate in the standard tax system. MSMEs must have adequate tax knowledge and competence to comply with their tax obligations after they enter the standard tax system. The research aims to develop a strategy for transitioning to a normal tax system from the perspective of both the taxpayer and the government, including the barriers encountered. This study used a qualitative approach and an in-depth interview to obtain data. A review of the literature was conducted, as well as in-depth interviews with DGT officials, tax scholars, tax practitioners, and SME taxpayers. The most recent rule on final income tax for MSMEs establishes a time restriction for applying the final income tax rate and recording. The grace period was designed to teach MSMEs how to manage their bookkeeping and other obligations under the conventional tax system while growing their business. According to the study’s findings, MSMEs taxpayers do not have a distinct strategy for dealing with the conventional tax system. They do, however, have commercial plans that overlap with the transition strategy. On the other hand, the government, through DGT, launched a plan called Business Development Services. The challenges of human resources and initiative affect both government and MSMEs taxpayers. This article examines the strategic procedures necessary to convert MSME taxpayers from a presumptive tax regime to the implementation of a conventional tax system, as well as the barriers encountered in achieving tax equity. The report proposes a transition strategy from a presumptive, tax regime to the implementation of a conventional tax system on the hard-to-tax sector by the Indonesian tax authorities and MSME taxpayers.